Amblyomma testudinarium infestation on a brown bear (Ursus arctos yesoensis) captured in Hokkaido, a northern island of Japan - Nakao, Ryo; Shinjo, Kohei; Sakiyama, Tomoki; Ogata, Shohei; Kusakisako, Kodai; Kinoshita, Gohta; Naguib, Doaa; Chatanga, Elisha; Mohamed, Wessam Mohamed Ahmed; Moustafa, Mohamed Abdallah Mohamed; Matsuno, Keita; Ito, Takuya; et al. (Parasitology international, 2021)
The tick Amblyomma testudinarium Koch, 1844 (Acari: Ixodidae) is known as a vector of several pathogens such as Rickettsia tamurae and severe fever with thrombocytopenia syndrome (SFTS) virus. This tick species is present in many Asian countries, including Japan, where its distribution is limited to the warm areas of Kanto region and the southwestern region. The present study reports the recovery of a partially engorged A. testudinarium from a wild brown bear captured in Shari town, Hokkaido. In addition to morphological identification, the specimen was genetically characterized by the complete mitochondrial genome sequencing. The results showed that the length of the obtained mitogenome is 14,835 bp that encodes 13 protein-coding, two ribosomal RNA (rRNA) (12S and 16S), and 22 transfer RNA genes with two non-coding control regions. The phylogenetic analysis indicated that our sample clustered with A. testudinarium from Nara, Japan, but separated from A. testudinarium from China. Although the introduction of the tick through livestock transportation cannot be ruled out, the detection of A. testudinarium in Hokkaido prefecture, which is separated from the main island where A. testudinarium is present in the south, may suggest the introduction by migratory birds. This study provides important insights on the distribution and host range of A. testudinarium. This will be useful for the future taxonomic analysis of ticks based on the complete mitogenome sequencing. To our knowledge, this is the northernmost detection point of the tropical tick A. testudinarium. •Amblyomma testudinarium was collected from a brown bear captured in Hokkaido.•The complete mitochondrial genome of Amblyomma testudinarium was determined.•The tick was negative by PCR/RT-PCR for piroplasms, rickettsiae, and SFTSV infection.